Baby bear, baby bear, what do you see? - Martin, Bill, 1916-2004.; Carle, Eric (New York : Holt, 2007)
Illustrations and rhyming text portray a young bear searching for its mother and meeting many North American animals along the way.
Pub Weekly
School Library Journal
Wilson's Children
Booklist, June 2007
Horn Book, April 2008
Kirkus Review, July 2007
Keywords: Animals -- North America -- Juvenile fiction; Bears -- Juvenile fiction; Mother and child -- Juvenile fiction; Animals -- Fiction; Bears -- Fiction; Mother and child -- Fiction; Stories in rhyme; Animals -- Fiction; Bears -- Fiction; Mother-child relationship -- Fiction; Stories in rhyme; Picture books for children